2013
DOI: 10.1002/erv.2256
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Neuromodulation on Eating and Body Weight: Evidence from Human and Animal Studies

Abstract: Neuromodulation tools have potential for reducing ED symptomatology and related behaviours, and for altering food intake and body weight. In response to such findings, and emerging neural models of ED, treatment approaches are highly unlikely to remain 'brainless'. More research is required to evaluate the potential of neuromodulation procedures for improving long-term outcomes in ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
95
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 126 publications
8
95
0
6
Order By: Relevance
“…Previous studies provide evidence of positive effects of neuromodulation techniques (i.e., repetitive transcranial magnetic stimulation [rTMS]) on eating disorder symptomatology in individuals with bulimic-type eating disorders. [51][52][53] Repetitive transcranial magnetic stimulation of the dorsolateral PFC in individuals with bulimic-type eating disorders resulted in lower cue-induced food cravings and could therefore reduce binge eating. A recently published study reported rTMSinduced decreases in cerebral oxygenation of the left dorsolateral PFC in patients with bulimia nervosa using near-infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provide evidence of positive effects of neuromodulation techniques (i.e., repetitive transcranial magnetic stimulation [rTMS]) on eating disorder symptomatology in individuals with bulimic-type eating disorders. [51][52][53] Repetitive transcranial magnetic stimulation of the dorsolateral PFC in individuals with bulimic-type eating disorders resulted in lower cue-induced food cravings and could therefore reduce binge eating. A recently published study reported rTMSinduced decreases in cerebral oxygenation of the left dorsolateral PFC in patients with bulimia nervosa using near-infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…EDs are characterized by altered self-image and maladaptive eating behaviors, and include AN, bulimia nervosa (BN) and binge-eating disorder (BED; McClelland et al, 2013). In recent years, functional imaging studies of EDs have pinpointed the intersection of cognitive and reward systems as integral to eating behavior regulation (Val-Laillet et al, 2015).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…Interestingly, prefrontal regions showed also different food-related activity depending on individual differences in reward drive, emotional eating style and cognitive restraint of eating (Beaver et al, 2006;Blechert, Goltsche, Herbert, & Wilhelm, 2013;Hollmann et al, 2012); finally, the activation of the prefrontal cortex differed when healthy volunteers were compared to participants with eating disorders such as obesity or anorexia (Martin et al, 2010;Uher et al, 2004). These results have led researchers to consider the prefrontal cortex as part of a neural circuit contributing to the pathophysiology of eating disorders (Kaye, Wagner, Fudge, & Paulus, 2011) and therefore an interesting candidate as cortical target for studies aiming at exploring the modulatory effects of non-invasive brain stimulation techniques on food-related behaviour (McClelland, Bozhilova, Campbell, & Schmidt, 2013). Indeed, medial and dorsolateral prefrontal cortices have been selected as target sites in studies with transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS) showing that stimulation sessions reduced food craving in healthy participants (Fregni et al, 2008;Goldman et al, 2011;Uher et al, 2005) and pathological feelings and behaviour in participants with eating disorders (Downar, Sankar, Giacobbe, Woodside, & Colton, 2012;Van den Eynde et al, 2010;Van den Eynde, Guillaume, Broadbent, Campbell, & Schmidt, 2013).…”
Section: Introductionmentioning
confidence: 96%